2022
DOI: 10.1002/asi.24653
|View full text |Cite
|
Sign up to set email alerts
|

Team power dynamics and team impact: New perspectives on scientific collaboration using career age as a proxy for team power

Abstract: Power dynamics influence every aspect of scientific collaboration. Team power dynamics can be measured by team power level and team power hierarchy. Team power level is conceptualized as the average level of the possession of resources, expertise, or decision‐making authorities of a team. Team power hierarchy represents the vertical differences of the possessions of resources in a team. In Science of Science, few studies have looked at scientific collaboration from the perspective of team power dynamics. This … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 74 publications
(89 reference statements)
0
3
0
Order By: Relevance
“…Xu et al (2022a) took the career age as the basis of power, where senior researchers have more rights in decision‐making than junior researchers. By analyzing teams in Computer Science, Physics, Sociology, Library & Information Science, and Arts & Humanities, Xu et al (2022a) calculated the mean value and Gini coefficient of team members' career age to represent the team power level and team power hierarchy. Finally, they found that a flat structure at different team power levels can have higher team citations.…”
Section: Related Workmentioning
confidence: 99%
See 2 more Smart Citations
“…Xu et al (2022a) took the career age as the basis of power, where senior researchers have more rights in decision‐making than junior researchers. By analyzing teams in Computer Science, Physics, Sociology, Library & Information Science, and Arts & Humanities, Xu et al (2022a) calculated the mean value and Gini coefficient of team members' career age to represent the team power level and team power hierarchy. Finally, they found that a flat structure at different team power levels can have higher team citations.…”
Section: Related Workmentioning
confidence: 99%
“…A researcher's career age, previous citation, H‐index, previous collaborators, productivity, function, and role can also be taken as the proxy of power since they represent prestige, resources, knowledge, and experience (Merton, 1973). Xu et al (2022a) took the career age as the basis of power, where senior researchers have more rights in decision‐making than junior researchers. By analyzing teams in Computer Science, Physics, Sociology, Library & Information Science, and Arts & Humanities, Xu et al (2022a) calculated the mean value and Gini coefficient of team members' career age to represent the team power level and team power hierarchy.…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation